Selected aspects of water and sewage management in Poland in the context of sustainable urban development - Lewandowska, Aleksandra; Piasecki, Adam (Bulletin of Geography. Socio-economic Series, 2019)
Effective water and sewage management is one of the most important enablers of sustainable urban development. In Poland, water and sewage management has been undergoing systematic transformation since the 1990s. This process intensified with Poland’s accession to the European Union in 2004. The aim of the work is to analyse and evaluate water and sewage management in cities in Poland in terms of sustainable development. This was made possible by selecting seven variables from which a summative index (SI) was calculated. The analysis revealed a number of positive changes that have occurred in this field. These were mainly: a decrease in water consumption in households and industry, and an increased share of wastewater treated biologically or using enhanced nutrient removal in total wastewater. An increase in SI was found in 98% of the researched cities. The largest improvement in water and sewage management took place in cities of populations below 100,000 and little industry, and in three large cities, namely Warsaw and Szczecin.